Reduction of Total Harmonic Distortion (THD) on Multilevel Inverter with Modified PWM using Genetic Algorithm - Raharja, Lucky Pradigta Setiya; Q., Ony Asrarul; Arief, Zainal; Windarko, Novie Ayub (EMITTER International Journal of Engineering Technology, 2017)
In this research, modified PWM has been applied to the multilevel inverter (MLI) single-phase three-level diode clamp full bridge. Modified PWM is performed to produce minimum Total Harmonic Distortion (THD) the voltage because the quality of the good voltage is indicated by small THD. The THD indicates the quality of AC voltage source. The THD standard by the IEEE STD 519-1992 Harmonic Voltage Limits is 5% and the Pacific Corp standard is 8%, if the THD value is greater than the THD standard it can cause the electronic load to be damaged due to the damaged waveform. Modified PWM is applied by adding a 50 Hz sinusoidal reference signal with a sinusoidal signal which has a certain amplitude, frequency and phase shift angle. The frequency of the adder signal is the frequency at which the value of the individual harmonic voltage appears (n harmonic). To get maximum result, optimization using Genetic Algorithm (GA) method to determinate amplitude & phase shift angle done. The result of implementation hardware with modified PWM shows smaller THD voltage compared to the THD voltage with Sinusoidal Pulse Width Modulation (SPWM) switching up to 0.19 or decrease 65,51 % for modified PWM of harmonic injection n = 7 with GA optimization ma= 0.8 (A=0.0936 and Ã¸ = 0 rad) and up to 0.08 or decrease 12,30 % for modified PWM of harmonic injection n = 22 with GA optimization ma = 0.4 (A=0.1221 and Ã¸ = 0 rad).